Seasonal Variability on Microplastic Polutions In Water and Sediment of Ciliwung River - Wilyalodia, Hefty Clarissa; Tybeyuliana, Elgrytha Victoria; Mahendra, Alloysius Pamurda Dhika; Pratama, Mochamad Adhiraga; Rahmawati, Suphia; Iresha, Fajri Mulya; Moersidik, Setyo Sarwanto (CSID Journal of Infrastructure Development, 2023)
Microplastics, recognized as emerging contaminants, have been detected in numerous rivers globally. This study focuses on the Ciliwung River in Jakarta, examining the influence of seasonal variations—specifically the rainy and dry seasons—on microplastics' concentration, types, and colors. Sampling was conducted during November 2022 (dry season) and March 2023 (wet season) using a plankton net for water (10 liters) and an Ekman grab sampler for sediment (400 mililiters). Microplastic abundance was analyzed following the National Oceanic and Atmospheric Administration (NOAA) adaptation method, and their material characteristics were identified using Fourier Transform Infrared Spectroscopy (FTIR) testing. Results revealed a notable seasonal impact: in the dry season, average microplastic abundance was 530 particles/liter in water and 859 particles/100 grams in sediment, whereas, in the wet season, these figures rose to 1,111 particles/ liter and 1,583 particles/100 grams, respectively. Fragments were the predominant type of microplastics, and black was the dominant color in both seasons. This consistency suggests similar sources and activities contributing year-round to microplastic pollution in the Ciliwung River.